Investigation on electrochemical performance of striped,?12 and x3 Borophene as anode materials for lithium-ion batteries - Karimzadeh, Sina; Safaei, Babak; Jen, Tien-Chien (Elsevier Science Inc, 2023)
By developing next-generation lithium-ion batteries (LIBS), demand for exploring novel anode materials with exclusive electrochemical features and ultra-high capacity is increasing. In the current research, first-principles theory, and density functional theory (DFT) calculations were conducted to extensively investigate and compare the capability of three different borophene nanolayers, including striped, beta 12, and x3 borophene, as a novel candidate for anode electrode in LIBs. We first predicted the most preferential Li atom adsorption sites on the three borophene structures. The predicted average formation energies for striped, beta 12, and x3 borophene were obtained 3.123, 3.184, and 3.216 eV, respectively. The positive value of formation energy exhibits the sufficient stability of the structures. Moreover, the negative adsorption energy proved that Li atom insertion on all bor-ophene monolayers is thermodynamically favorable. In order to simulate the lithiation process, we gradually increased the concentration of Li atoms. We found that the fully lithiated striped, beta 12 and x3 borophenes could provide ultra-high specific capacities of 1700, 1983, and 1859 mAh/g, respectively. Structural analysis proved that the surface area expansion rate of the striped borophene in a fully lithiated state was 1%, which was lower than those of beta 12 and x3 borophene with 3.33% and 2.63%, respectively. The analyses of electronic properties confirmed that borophenes were inherently metallic and superior ion conductive agents, even after fully lithiated state. Ion diffusion was studied using Nudged elastic band method and the value of diffusion energy barrier ranged from 0.03 to 0.36 eV which was lower than other promising 2D anode materials. Furthermore, open-circuit voltage results demonstrated that the electronic potential of modeled borophenes was low enough to be in the acceptable range of under 1.2V. All these reports exhibited that borophene nanolayers with excellent specific capacity and superior conductivity were desired candidates for anode materials of next generation LIBs.
Keywords: Energy storage; Lithium-ion batteries; Anode materials; Borophene; DFT